Study of the Effect of Squalene Epoxidase Activity on Squalene Biosynthesis by Yeast Saccharomyces Cerevisiae VGSh-2 - Meshcheryakova, Olga L.; Shuvaeva, Galina P.; Sviridova, Tatyana V.; Tolkacheva, Anna A.; Korneeva, Olga S. (KnE Life Sciences, 2022)
The researchers of this study investigated the biosynthesis of squalene by the yeast S. cerevisiae VGSH-2 through the activity of squalene epoxidase, which is a key enzyme in the conversion of squalene to ergosterol. It has been established that under aerobic conditions the antimycotic drug terbinafine promotes the switching of ergosterol formation to squalene synthesis. This switch occurs through specific inhibition of the squalene epoxidase of the yeast S. cerevisiae VGSH-2, thus increasing the biosynthetic ability of the yeast towards squalene. According to the results of this study, the optimal concentration of terbinofine in the nutrient medium was 0.3 μmol / cm3 . This concentration led to a 5-fold decrease in squalene epoxidase activity and a 7-8 times increase in squalene synthesis. The results obtained can be used to develop a competitive technology for the industrial production of squalene by microbial synthesis. Keywords: squalene, yeast, biosynthesis, inhibition of activity, terbinafine, squalene epoxidase, Saccharomices cerevisiae VGSH-2